Investigating the Cognitive Theories of Career Development - Seyed Hamid Reza Fatemi Aghda; Seyed Mohammad Tabataba'i Nasab; Mehdi Sabokro (مدیریت دولتی, 2018)
Objective: There are several theories proposed on the career development and researchers have classified these theories in different categories. Career-related cognitive theory is one of the latest categories including two theories: social cognitive theory of career development and cognitive information processing. The current study seeks to compare these two cognitive theories of career development by identifying the criteria for comparison of theories. Methods: The present study is a practical research from goal perspective, is an exploratory survey in nature and methodologically is categorized in the field of mixed research. To collect data, a sample of 20 academic experts and active managers in human resource management and career development were interviewed. Results: To execute the research, 34 criteria were identified based on theoretical foundations and 12 criteria were agreed upon according to experts' opinions; finally, the two theories were compared using a fuzzy Delphi technique and those criteria. Conclusion: The results showed that social cognition of career development theory mostly emphasizes on environment, future, and generalizability respectively, while cognitive information processing theory mainly emphasizes on the job, individual, process, and the organization.